Characterization and Investigation on Photocatalytic Activities of TiO2/Coconut Shell-Based Activated Carbon - Sheilatina Sheilatina; Surya Lubis; Fathurrahmi Fathurrahmi; Amalia Oktari (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2021)
Coconut shell-based activated carbon-supported TiO2 catalyst had been prepared with a sol-gel method using titanium tetraisopropoxide acting as TiO2 precursor. TiO2/activated carbon photocatalyst was characterized with X-Ray Diffraction (XRD), Fourier Transform-Infrared (FT-IR), Scanning Electron Microscopy-Energy Dispersive X-Ray (SEM-EDX), and surface area analysis using Brunauer–Emmett–Teller (BET) adsorption-desorption isotherm. Photocatalytic activities of TiO2/activated carbon were investigated through the degradation of indigo carmine using UV light. The highest degradation percentage (%D) obtained for the indigo carmine was 91.79% at pH 3 and an initial concentration of 5 mg L-1 after 25 min radiation. TiO2/activated carbon showed higher photocatalytic activities when sunlight was used, in comparison to that of UV light.